Model Pemberdayaan dan Pengembangan Potensi Sumber Daya Lokal Berkelanjutan pada Desa Kangkung Kecamatan Mranggen Kabupaten Demak - Stacia Reviany Mege; Rianditha Eri Werdani; Nurul Imani Kurniawati; Kholidin Kholidin (Jurnal Pengabdian Pada Masyarakat, 2020)
MODEL OF EMPOWERMENT AND DEVELOPMENT OF LOCAL RESOURCE POTENTIAL IN KANGKUNG VILLAGE, MRANGGEN SUBDISTRICT, DEMAK REGENCY IN ORDER TO CONTINUOUSLY IMPROVING THE STANDARD OF LIVING OF COMMUNITIES. Kangkung Village is located in Mranggen Subdistrict, Demak Regency, Central Java and rich in natural resources and other potentials. However, the local potentials are not well utilized due to lack of funding, technology, skill, and knowledge of the communities. Some sectors such as farming or gardening have been the main source of income for most of the villagers even though the disparity between village and cities is increasing. The purpose of this community service is to empower the community to realize their potential and to take action and move together for the prosperity of all villagers. Methods used to obtain the objective were socialization and assistance. The result of the community service was the identification of problems, solutions, and potential in Kangung Village. Furthermore, the community realized that local resource potential does not rely on natural resources only but more to human resources that they are motivated to improve their potential. In conclusion, socialization and assistance are needed by the village to realize their potential and must be done continuously and the collaboration between the community and village administrators is highly necessary to improve the standard of living.